Consumers’ Intention to Use Renewable Energy Based on the Behavioral Reasoning Theory - GOBEL, Tessy Fitriyani; RAMADHAN, Medya; PRATAMA, Iden Aksana Putra; HENDRIANA, Evelyn (Journal of Environmental Management and Tourism; Vol 15 No 1 (2024): JEMT, Volume XV, Issue 1(73), Spring 2024, 2024)
Public concerns about climate change and environmental protection have triggered governments and corporations to do research on clean and cost-effective forms of energy. Green energy is relatively new in developing countries, which results in limited market penetration and low consumer acceptance. This study aims to investigate the relationship between global motives and consumer intentions to use renewable energy via the Behavioral Reasoning Theory (BRT). In this research, reasons for supporting the utilization of renewable energy are shown through environmental concerns and perceived benefits, while reasons against it are represented through perceived costs. An online survey obtained 275 valid data responses from Indonesian middle- and upper-class consumers. This data was analyzed using PLS-SEM to maximize the model's predictive value. All hypotheses tested, except for the effect of environmental concern and perceived cost on attitude, were proven to influence customer intentions to use renewable energy. This study found that perceived benefits gave the largest contribution to global motives for using renewable energy. Since this study involved consumers from the middle to upper class in developing countries, perceived behavioral control had the most influence on intention to use renewable energy compared to attitude and subjective norms.